Insights into hospitalisation of advanced cancer patients: a study of medical records. (22nd April 2015) - Bostanci, Adam; Horey, Dell; Jackson, Kate; William, Leeroy; Pittmann, Lise; Ward, Jennifer; Moore, Gaye; Martin, Peter; Hudson, Peter; Philip, Jennifer
Abstract : The aim of this study was to explore reasons for the hospitalisation and place of death outcomes of terminal cancer patients. The methodology involved a qualitative content analysis of medical records pertaining to the last 3 months of life of 39 patients with one of four malignancies: prostate, breast, lung, or haematological. The results presentation is organised around three themes: decision hierarchy in health care, meanings of 'home', and late recognition of dying. Based on the detailed findings, this paper suggests that important insights into the broader goals of advanced cancer patients are offered by allied health staff, and that more effective use of the multidisciplinary team may support endeavours to achieve more home deaths for cancer patients who want this outcome. The analysis also provides new insights into the meaning of 'home' in interactions between advanced cancer patients and health professionals. The wish for 'home' appears bound up with other patient goals and the implications of this are discussed.